Study of the effect of wind direction on ship helideck using computational fluid dynamics - Fauzi, AH Fauzi; Silalahi, NH Silalahi (Trigin Publisher, 2025)
The safety and aerodynamic stability of a ship's helideck is a crucial factor in maritime flight operations, especially in variable wind conditions. One of the main challenges is the interaction between the airflow and the ship's structure which can create turbulence and recirculation zones that affect the stability of the helicopter during takeoff and landing. This study aims to analyze the airflow characteristics around the ship's helideck at various wind incidence angles using the Computational Fluid Dynamics (CFD) method. The simulation model includes ship and helideck geometry modeling, with boundary conditions set at 1 atm atmospheric pressure, 298 K temperature, and 10 m/s wind speed at angles of 0° to 180°. The simulation results show that the maximum pressure occurs at a 90° angle, while the maximum velocity of the airflow is recorded at a 0° angle. Recirculation zones and air vortices are significantly formed at small angles such as 150°, which can destabilize the helicopter. These findings emphasize the importance of helideck design optimization and aerodynamic mitigation strategies to improve flight safety. The limitation of this study lies in the lack of quantitative measurement of the intensity of the vortex, so further research is recommended to integrate experimental validation and more complex turbulence models to strengthen the reliability of the results.